The management of cardiovascular disease risk factors in bipolar disorder patients in primary healthcare settings (Revista Puertorriqueña de Psicologia, 2020)
Accumulating evidence supports the association between cardiovascular disease (CVD) risk factors and bipolar disorder (BD). CVD is the leading cause of morbidity and mortality in patients with bipolar disorder. However, there is a need to study the management of the risk factors in the primary healthcare context. This narrative review aims to appraise the different approaches of care that have been used in the management of these patients to address CVD risk factors in primary care. We reviewed articles from PubMed, Science Direct and other relevant to our search. The keywords used for this review included “bipolar,” “bipolar disorder,” “cardiovascular” or “metabolic syndrome,” “screening,” “primary care,” and “integrative” or “integrated care model” or “collaborative care model.” This review includes studies published over a period of 48 months (January 2016 through December 2019). We used the study-quality assessment tools from the National Heart, Lung, and Blood Institute to assess the quality of the articles found. CVD risk factors in patients with BD and forms of other severe mental illness (SMI) are often underdetected. Primary healthcare providers need to identify these risk factors in the management of these patients to determine and recommend appropriate strategies.